Philological Studies on Ahmad Mutamakkin Court in Kajen Text Perspective - Miftakhul Munif; Mohamad Agus Jauhari; Muhammad Khotib; Khoirotun Nisa’; Maulidatul Ahadiah (Santri: Journal of Pesantren and Fiqh Sosial, 2022)
The Kajen Text Manuscript is a very important reference regarding the history of Haji Ahmad Mutamakkin, which the hands of philologists have not touched. This philological research aims to find out the trial process of Haji Ahmad Mutamakkin from the perspective of the Kajen community through the Kajen Text. This type of research is qualitative research with a philological approach that seeks to answer problems through library research. The results of this study inform that Kajen's text places Haji Ahmad Mutamakkin as a respected faqih because of his far-reaching and broad views. As a professor of religion, Mutamakkin preached from one place to another, which was considered the right target. The accusation of heresy is the implication of a leaflet that intends to corner Mutamakkin. The Kajen's text describes the trial of Mutamakkin's case, which shows Mutamakkin's expertise in providing arguments for his convictions. An advantage possessed by Mutamakkin as described in Kajen's text is his firmness in upholding the principles of establishing his creed. His demeanor seemed calm, and he looked elegant in front of the audience. Kajen's text states that the King eventually became Mutamakkin's disciple after following Mutamakkin's allegiance to teachings, ending with Mutamakkin's acquittal of all his charges.